Perspektif Guru Terhadap Pengembangan Keterampilan Berbahasa Makracalis Serta Implementasinya Terhadap Pembelajaran Bahasa Indonesia - Nur Rahmadani; Yola Yunita; Sawalichia Kusuma Ningrum (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to explore teachers' perspectives on the development of Makracalis language skills and their implementation in Indonesian language learning. The research method uses interviews with Indonesian language teachers from various levels of education. The results show that developing Makracalis language skills requires a holistic and diverse approach, with the 5M strategy (fun classes, motivation, humor, rewards, student participation) being the key in increasing students' interest in learning the language.